1998
DOI: 10.1210/mend.12.4.0083
|View full text |Cite
|
Sign up to set email alerts
|

Differential Use of Transcription Activation Function 2 Domain of the Vitamin D Receptor by 1,25-Dihydroxyvitamin D3 and Its A Ring-Modified Analogs

Abstract: Analogs of 1,25-dihydroxyvitamin D3 (1,25D3) can be used to elucidate details of vitamin D receptor (VDR) activation. The A ring-modified analog, (TN-2) has 15-fold less affinity for VDR, but its transcriptional activity is diminished 1000-fold. Likewise, the ability of TN-2 to induce a protease-resistant conformation in VDR is 1/1000 that of 1,25D3. The stability of the VDR-TN-2 complexes is also significantly lower than VDR-1,25D3 complexes. Mapping the VDR-binding site of TN-2 showed that it had a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…Recently, deletion-mutation analysis revealed that an activation domain of VDR is required for the interaction between VDR and SRC-1 (32 this ligand-dependent interaction between SRC-1 and VDR was observed in Saos-2 cells, but not in HeLa cells in our system. In Saos-2 cells, the interaction between VDR and SRC-1 was reduced by TEI-9647, suggesting that the conformational change of VDR elicited by the ligand differs between 1␣,25(OH) 2 D 3 and TEI-9647 as suggested by studies using other vitamin D analogues (22,33,34).…”
Section: Tei-9647 Inhibited the Vdr And Rxr Heterodimer Formation Detmentioning
confidence: 91%
“…Recently, deletion-mutation analysis revealed that an activation domain of VDR is required for the interaction between VDR and SRC-1 (32 this ligand-dependent interaction between SRC-1 and VDR was observed in Saos-2 cells, but not in HeLa cells in our system. In Saos-2 cells, the interaction between VDR and SRC-1 was reduced by TEI-9647, suggesting that the conformational change of VDR elicited by the ligand differs between 1␣,25(OH) 2 D 3 and TEI-9647 as suggested by studies using other vitamin D analogues (22,33,34).…”
Section: Tei-9647 Inhibited the Vdr And Rxr Heterodimer Formation Detmentioning
confidence: 91%
“…We (16) and others (30) have shown that the transactivation potency of an analog of 1,25D 3 may be determined by its ability to induce VDR to assume a protease-resistant conformation. To examine whether this aspect of ligand interaction with the receptor indeed was impaired by the H305Q mutation, we performed quantitative protease sensitivity assays.…”
Section: Synthetic Analogs Restore Defective Vitamin D Receptor Actionmentioning
confidence: 92%
“…The proposed mechanism for this enhanced potency is that in which the analog changes the conformation of the VDR to provide a more effective interface for interaction with RXR and transcription coactivators. Second, even analogs that are less potent transcriptionally than 1,25D 3 may contact different amino acid residues in the ligand-binding pocket such that they have the potential to bind and activate VDRs with mutations at the usual contact points for the hormone (15,16).…”
Section: Hereditary Vitamin D-resistant Rickets (Hvdrr)mentioning
confidence: 99%
See 2 more Smart Citations